Population‐based human papillomavirus infection and genotype distribution among women in rural areas of South Central Ethiopia. Issue 3 (8th September 2020) - Teka, Brhanu; Gizaw, Muluken; Ruddies, Friederike; Addissie, Adamu; Chanyalew, Zewditu; Skof, Anna Sophie; Thies, Sarah; Mihret, Adane; Kantelhardt, Eva Johanna; Kaufmann, Andreas M.; Abebe, Tamrat
Abstract: In Ethiopia, cervical cancer is the second leading cause of morbidity and mortality from all cancers in women. Persistent infection with human papillomaviruses (HPV) plays a key role in the development of cervical intraepithelial neoplasia and invasive cervical cancer. To establish baseline data on the population‐based prevalence of HPV infection and genotype distribution, we investigated cervical HPV epidemiology among rural women. This population‐based study was conducted among rural women aged 30‐49 years in Butajira, south‐central Ethiopia. A total of 893 samples were tested from 1020 screened women. A self‐sampling device (Evalyn Brush, Rovers, Oss, The Netherlands) was used and HPV presence and genotype was determined using multiplexed genotyping (MPG) by BSGP5+/6+ PCR with Luminex read out. The HPV positivity rate was 23.2% (95% CI: 23.54‐22.86%) and 20.5% (95% CI = 20.79‐20.21) and 10.3% (95% CI = 10.52‐10.08) women were high‐risk (hr‐ and low‐risk (lr‐) HPV positive, respectively. Fifty five (7.2%) of the women showed multiple hr‐HPV infections. Age‐specific hr‐HPV infection peaked in the age‐group 30‐ to 34 years old (58.6%) and decreased in 35‐39, 40‐44 and 45‐49 years to 20.4%, 4.5% and 3.8% respectively. The top five prevalent hr‐HPV genotypes were HPV16 (57.1%), 35 (20.3%), 52 (15.8%), 31 (14.1%), and 45 (9.6%) in the Butajira district. As a first population‐based study in the country, our results can serve as valuable reference to guide nationwide cervical cancer screening and HPV vaccination programs in Ethiopia. Abstract : What's new? Infection with human papillomavirus (HPV) is the primary cause of cervical cancer, a disease that is most prevalent in developing countries. Population‐based HPV data is crucial for cervical cancer screening and vaccination programs. This is the first population‐based study in rural women in Ethiopia using self‐sampling. The authors found a high‐risk HPV positivity rate of 20.5% in the study area and a different list of top five prevalent high‐risk HPV genotypes compared to other studies worldwide. The findings will help guide national cervical cancer screening and vaccination programs in Ethiopia.